PEMETAAN KERAPATAN VEGETASI (NDVI) DAN SUHU PERMUKAAN (LST) UNTUK MENDUKUNG ADAPTASI PERENCANAAN KOTA TERHADAP PERUBAHAN IKLIM DI KOTA SEMARANG - Kris Sahara, Angga; Elysia, Vita (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
Climate change is a global issue with significant implications for urban planning. This study examines Vegetation Density (NDVI) and Land Surface Temperature (LST) in Semarang City to support climate-adaptive urban planning. Using Landsat 8 imagery data from 2015 and 2023, analyzed through a Geographic Information System (GIS) approach, the findings reveal a substantial decline in vegetated areas. The moderately dense vegetation category decreased by 1,085.13 hectares (10.82%), while non-vegetated areas expanded by 1,988.64 hectares (30.05%). Additionally, there was a significant rise in surface temperature, from a maximum of 28.445°C in 2015 to 35.730°C in 2023. A strong negative correlation between NDVI and LST indicates that vegetation loss contributes to increased temperatures. To mitigate these effects, this study recommends adaptation strategies such as enhancing urban vegetation, expanding green open spaces, and implementing sustainable water management. These measures are expected to assist policymakers in developing strategies to enhance urban resilience to climate change.